The pan Indian ocean science congress at Perth (West Australia), 17-24 August 1954. (MAUSAM, 1954)
The formal opening of the Congress took place with due ceremony, at the beautiful Winthrop Hall of the West Australian University at Perth , on tho 17th night, the delegates from the various countries (viz. Australia, Burma, Ceylon, France, India, Indonesia, Malaya, Netherlands, Pakistan lowing delegation, representing the various and Portugal) being presented .